Adult learning in the digital age: Information technology and the learning society - Selwyn, N; Gorard, S; Furlong, J (Routledge Taylor and Francis Group, 2005)
This engaging book sheds light on the ways in which adults in the twenty-first century interact with technology in different learning environments. Based on one of the first large-scale academic research projects in this area, the authors present their findings and offer practical recommendations for the use of new technology in a learning society. They invite debate on: Why ICTs are believed to be capable of affecting positive change in adult learning. The drawbacks and limits of ICT in adult education. What makes a lifelong learner. The wider social, economic, cultural and political realities of the information age and the learning society. Adult Learning addresses key questions and provides a sound empirical foundation to the existing debate, highlighting the complex realities of the learning society and e-learning rhetoric. It tells the story of those who are excluded from the learning society, and offers a set of strong recommendations for practitioners, policy-makers, and politicians, as well as researchers and students. © 2006 Neil Selwyn, Stephen Gorard and John Furlong. All rights reserved.